(untitled) - Warren, Kenneth (London, 1976)
This book introduce about location choice and locational values. Facto mobility, technical change, and regional economic growth. Evolution and intervention in heavy industry location patterns.
Keywords: Vị trí công nghiệp,Industrial location; Nước Anh,Great Britain